Eliminating on the divergences o f the photon self - energy diagram in (2+1) dimensional quantum electrodynamics - Nguyen, Suan Han (H. : ĐHQGHN, 2017)
The divergence of the photon self-energy diagram in spinor quantum electrodynamics in (2 + 1) dimensional space time- (QEDs) is studied by the Pauli-Villars regularization and dimensional regularization. Results obtained by two different methods are coincided if the gauge invariant of theory is considered carefully step by step in these calculations.